2011
DOI: 10.1038/hr.2011.130
|View full text |Cite
|
Sign up to set email alerts
|

Association of a fat-derived plasma protein omentin with carotid artery intima-media thickness in apparently healthy men

Abstract: Obesity is causally linked with the development of atherosclerosis. Omentin is an adipocytokine whose concentrations are reduced in obese individuals. Here we examined the relationship between plasma omentin levels and carotid intima-media thickness (IMT), a marker of early atherosclerosis, in apparently healthy Japanese men. Participants were 100 Japanese men who underwent a medical checkup. Maximal IMT (max-IMT) and mean-IMT in common carotid artery were measured by highresolution carotid ultrasound system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…[13][14][15][16][17][18][19] Recent reports have usually demonstrated an inverse association between omentin-1 and atherosclerosis (AS). 18,[20][21][22][23] Little is known about omentin-1 in CKD. It may be implicated in the pathogenesis of CVD in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Recent reports have usually demonstrated an inverse association between omentin-1 and atherosclerosis (AS). 18,[20][21][22][23] Little is known about omentin-1 in CKD. It may be implicated in the pathogenesis of CVD in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma omentin levels are decreased in association with obesity-linked metabolic disorders, including metabolic syndrome, type 2 diabetes, and insulin resistance (9)(10)(11). Recent clinical studies have shown that circulating omentin concentrations are reduced in patients with cardiovascular disorders such as carotid atherosclerosis and coronary artery disease (12)(13)(14)(15). Thus, omentin may be a valuable biomarker for obese complications.…”
mentioning
confidence: 99%
“…Omentin is detectable in human blood stream (100 to 800 ng/ml) (11,12), and circulating omentin levels are decreased in obesity (11). Furthermore, circulating omentin levels are down-regulated in association with obesity-linked disorders, including type 2 diabetes, metabolic syndrome, endothelial dysfunction, carotid atherosclerosis, and coronary artery disease (12)(13)(14)(15)(16). It has been shown that treatment of adipocytes with the omentin protein results in enhancement of glucose uptake (8).…”
mentioning
confidence: 99%